Park city leads the way of urban development and innovation in China - Bai, Xiaohang; Sadia, Sehrish (Journal of Environmental Engineering and Landscape Management, 2023)
Cities have been the cradle of human civilization, with ongoing efforts to achieve the ideal city. Park cities prioritize “public” and “fair” principles in urban governance, emphasizing people-centered and livable spaces. This paper explores research hotspots and trends in park city evolution to support sustainable spatial planning. Analyzing 2278 articles covering country cooperation, research topics, and practices, the initial focus is on eco-city development, shifting towards ecological restoration and sustainable cities. Research focuses on urban gardens, ecological/cultural services, green spaces, and spiritual comfort. China’s park city construction faces challenges in spatial patterns, ecological functions, and human settlement, requiring attention in planning and management. More data, methods, and experiences are needed to inform science-policy planning in urban management, advancing sustainable pathways for people and nature.